Human Security in the Management of Indonesian Migrant Workers Post-Deportation from Malaysia in Batam City - M. Ferdi Septianda; Rizky Octa Putri Charin (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2025)
The deportation of Indonesian Migrant Workers (PMI) from Malaysia causes complex physical, psychological, and economic issues. This study aims to examine the management of deported PMI in Batam City by BP3MI Riau Islands. This research employed a descriptive qualitative method with data collection through interviews, observation, and documentation. Data analysis involved reduction, display, and conclusion drawing based on the UNDP (1994) Human Security theory covering seven indicators. The results indicate that the management of PMI proceeds reasonably well. Personal, community, and political security are implemented through structured repatriation systems, identity verification, socialization of legal procedures, and identification of illegal brokers. Food, health, and environmental security are ensured through food provision, a tiered medical referral system, and adequate sanitation. However, economic security remains limited to meeting basic needs. This study concludes that while basic protection is fulfilled, economic empowerment aspects require further improvement.